Daniel Enstedt and Katarina Plank (eds): Eastern Practices and Nordic Bodies: Lived Religion, Spirituality and Healing in the Nordic Countries - Poutiainen, Ella (Temenos, 2025)
Book review of Daniel Enstedt and Katarina Plank (eds): Eastern Practices and Nordic Bodies: Lived Religion, Spirituality and Healing in the Nordic Countries. Palgrave McMillan, 2023, 306 pp.